Leaving on a jet plane? The effect of challenge–hindrance stressors, emotional resilience and cultural novelty on self-initiated expatriates' decision to exit China. Issue 1 (19th January 2021) - Jannesari, Milad T.; Sullivan, Sherry E.
Abstract : Purpose: The number of self-initiated expatriates (SIEs) is growing, yet we know relatively little about their work experiences, especially how they react to stress. The purpose of this study is to examine whether challenge and hindrance stressors influence SIEs' intent to remain as well as the possible influence of emotional resilience and cultural novelty upon these relationships. Design/methodology/approach: Data were collected from 249 SIEs working in China. Findings: As hypothesized, hindrance stressors were negatively related to the SIEs' intent to remain. Contrary to expectations, challenge stressors were not associated with intent to remain. Hindrance (challenge) stressors were negatively (positively) related to emotional resilience, and resilience mediated the relationship between stressors and intent to remain. Cultural novelty failed to moderate the relationship between emotional resilience and intent to remain and did not moderate the mediated effects of challenge stressors on intent to remain via emotional resilience. Cultural novelty did moderate the mediated effects of hindrance stressors on intent to remain via emotional resilience, but not in the hypothesized direction. Research limitations/implications: This study was cross-sectional. It examined SIEs working in China, and its findings may not be generalizable to SIEs working in other countries. Originality/value: This is the first study to examine how emotional resilience may mediate the relationship between stressors and SIEs' intent to remain and also considered the possible moderating effects of cultural novelty. In addition, unlike most studies that focus only on the negative outcomes of hindrance stressors, this study tested the possible positive effects of challenge stressors.